There's something hidden in it

Calculus Level 5

a n + 1 + 1 = ( n + 1 ) a n {a}_{n+1} +1 = (n+1){a}_{n}

Define an sequence { a n } n = 0 \lbrace a_{n} \rbrace_{n=0} by the iteration above. For what value of a 0 {a}_{0} will the iteration converge to some finite value?

Report your answer as first four digits of a 0 {a}_{0} (without rounding off). For example, if your answer is 3.141592653789 3.141592653789 \ldots then enter 3.141.


Interestingly in the complete number line there exists only one possible value of a 0 {a}_{0} , for which this iteration doesn't diverge (that's the interesting aspect of it)

The sequence diverge to positive infinity for any starting value larger than a 0 a_0 , and the sequence diverge to negative for any starting value smaller than a 0 a_0 .


The answer is 1.718.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Jake Lai
Mar 15, 2015

This isn't a very formal solution, so I apologise.

Starting off with a 0 a_{0} :

a 0 = a 0 a 1 = 1 ! a 0 1 a 2 = 2 ! a 0 2 ! 1 ! 2 ! 2 ! a 3 = 3 ! a 0 3 ! 1 ! 3 ! 2 ! 3 ! 3 ! \begin{array}{c}\ a_{0} = a_{0} \\ a_{1} = 1!a_{0}-1 \\ a_{2} = 2!a_{0}-\frac{2!}{1!}-\frac{2!}{2!} \\ a_{3} = 3!a_{0}-\frac{3!}{1!}-\frac{3!}{2!}-\frac{3!}{3!} \end{array}

Going on, we see that

a n = n ! × a 0 n ! 1 ! n ! 2 ! n ! n ! = n ! ( a 0 k = 1 n 1 k ! ) a_{n} = n! \times a_{0}-\frac{n!}{1!}-\frac{n!}{2!}-\ldots-\frac{n!}{n!} = n! \left( a_{0} - \sum_{k=1}^{n} \frac{1}{k!} \right)

The only way for a n a_{n} to converge as n n \rightarrow \infty is for

a 0 = k = 1 n 1 k ! a_{0} = \sum_{k=1}^{n} \frac{1}{k!}

Since our RHS is e 1 e-1 by the Taylor series of e x e^{x} , a 0 = e 1 1.718 a_{0} = e-1 \approx \boxed{1.718} . The sequence thus converges to 0 0 .

Yep! Correct! BTW, even ore fancy notation would be to write sum of permutations(which can be proven by using Gamma function) too like a n = n ! a 0 e ( Γ ( n + 1 , 1 ) n ! ) {a}_{n} = n!{a}_{0} - e(\Gamma(n+1,1) - n!)

a n = n ! ( a 0 + 1 ) e Γ ( n + 1 , 1 ) {a}_{n} = n!({a}_{0} +1) - e\Gamma(n+1,1)

This is because this will be the general term and not the above summation one. *From here too, e 1 e-1 can be easily found.

Kartik Sharma - 6 years, 2 months ago

Good job! This is right.

Raghav Vaidyanathan - 6 years, 3 months ago

Same way! awesome question though, looks hard at first sight ,

but it is necessary to first show that if the sequence does converge, its gonna be at 0, which can ofcourse be easily shown by using a n 1 = a n a_{n-1} = a_{n}

only then, we can claim that the only value is 1.718

Mvs Saketh - 6 years, 2 months ago
Neelesh Vij
Sep 14, 2016

The given relation is:

a n + 1 + 1 = ( n + 1 ) a n a_{n+1} +1 = (n+1)a_{n}

Divide by ( n + 1 ) ! (n+1)!

a n + 1 ( n + 1 ) ! + 1 ( n + 1 ) ! = a n n ! \dfrac{a_{n+1}}{(n+1)!} + \dfrac{1}{(n+1)!} = \dfrac{a_{n}}{n!}

Let a n n ! = T n \dfrac{a_{n}}{n!} = T_{n}

So we get

T n + 1 T n = 1 ( n + 1 ) ! T_{n+1} - T_{n} = - \dfrac{1}{(n+1)!}

Now as n n \to \infty a n + 1 = a n a_{n+1} = a_{n} so a = 0 a_{\infty} = 0

Solving the above sequence we get

a 0 = n = 0 1 n ! \displaystyle a_0 = \sum_{n=0}^{\infty} \dfrac{1}{n!}

a 0 = e 1 \therefore \boxed{a_{0} = e-1}

I think your summation (second to last) should start at $1$. Other than that, great solution!

Keller VandeBogert - 4 years, 7 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...